Wearable-derived heart rate variability across the menstrual cycle, hormonal contraceptive use, and reproductive life stages in females: A living systematic review - De Jager, E.; Caulfield, B.; Angelidi, E.; Macnamee,, B.; Holden, S. (Sports Medicine, 2026)
Background Heart rate variability (HRV) reflects autonomic nervous system function and can now be continuously monitored in real-world settings using wearable technology. However, the influence of ovarian hormones on HRV remains unclear, underscoring the need to synthesize evidence across the female lifespan. Objective To examine the association between ovarian hormone profiles and HRV measured by wearable/mobile devices. Design Living systematic review. Data Sources A comprehensive search was conducted in PubMed, Web of Science, IEEE Xplore, SPORTDiscus, and Embase from inception to December 2025. The search followed the Participant (females of any age), Exposure (ovarian hormone profiles), and Outcomes (HRV measured by wearable devices) framework, using a combination of MeSH terms and keyword adaptations. Quality was assessed for cohort studies using the Newcastle-Ottawa Scale. Eligibility Criteria All studies were independently double screened by title, abstract, and full text. Studies were eligible if they examined differences in HRV measured by a wearable device, across the menstrual cycle in naturally menstruating females, in response to exogenous ovarian hormones, or across another ovarian hormone state such as menopause or pregnancy. Results From 299 identified records, 16 studies were included. In naturally menstruating females, HRV was higher at the beginning of the cycle and lower toward the end, with differences in time-domain HRV ranging from 3 to 9%. Hormonal contraceptive users exhibited lower HRV, particularly in the late cycle. Additionally, HRV tended to decline after menopause with increasing age. The quality of evidence in this review was moderate (7/9). Variability in how menstrual cycle phases and menopausal status were classified across studies limited comparability and the ability to synthesize findings quantitatively. Conclusions Wearable-derived HRV is associated with differences across the menstrual cycle, oral contraceptive use, and reproductive life stages. This should be considered when presenting HRV metrics to female users. This may improve the interpretation of data for female athletes, patients, or women who track their HRV.